Fecal microbiota was reshaped in UCP1 knock-in pigs via the Adipose-Liver-Gut Axis and contributed to less fat deposition - Jianfei Pan; Linya Chui; Tianxia Liu; Qiantao Zheng; Xuexue Liu; Lulu Liu; Ying Zhao; Lilan Zhang; Min Song; Han Jianlin; Jiaojiao Huang; Chaohua Tang; et al. (American Society for Microbiology, 2023)
This article investigated the effect of the ectopic expression of UCP1 on the regulation of fecal microbiota composition and metabolites and which alters the fat deposition phenotype. Bacteria, including Oscillospira and Coprococcus , and the metabolite HDCA were found to be significantly increased in feces of UCP1 pigs and had a negative relationship with backfat thickness.